Universality and self-similar behaviour of non-equilibrium systems with non-Fickian diffusion - Kharchenko, D.O.; Kharchenko, V.O.; Kokhan, S.V. (Condensed Matter Physics, 2014)
Analytical approaches describing non-Fickian diffusion in complex systems are presented. The corresponding methods are applied to the study of statistical properties of pyramidal islands formation with interacting adsorbate at epitaxial growth. Using the generalized kinetic approach we consider universality, scaling dynamics and fractal properties of pyramidal islands growth. In the framework of generalized kinetics, we propose a theoretical model to examine the numerically obtained data for averaged islands size, the number of islands and the corresponding universal distribution over the island size. Наведено аналiтичнi методи щодо опису нефiкiвської дифузiї у нерiвноважних складних системах. Цi пiдходи застосовано до вивчення статистичних властивостей росту пiрамiдальних острiвкiв iз взаємодiючим адсорбатом при епiтаксiальному ростi. Використовуючи узагальнений кiнетичний пiдхiд, розглянуто
унiверсальнiсть, скейлiнгову динамiку та фрактальнi властивостi процесу росту пiрамiд. У рамках узагальненої кiнетики запропоновано теоретичну модель для пояснення чисельно отриманих даних для
середнього розмiру островiв, їх числа та вiдповiдної функцiї розподiлу за розмiрами.